PENGARUH SUHU DAN LAMA PENGERINGAN TERHADAP KADAR ZAT BESI BAYAM HIJAU (Amaranthus spp.) - Rahman, Siti Ayu; ansharullah, ansharullah; Faradilla, RH Fitri (Jurnal Sains dan Teknologi Pangan, 2020)
ABSTRACT This study aimed to determine the effect of temperature and drying time on the iron levels in green spinach (Amaranthus spp.). This study used a two-factor of Completely Randomized Design (RAL): the drying temperature consisting of three levels (50ºC (S1), 60ºC (S2) and 70ºC (S3)) and the treatment of drying time which consists of three levels (5 hours (T1), 6 hours (T2), and 7 hours (T3)). The data analysis in this study was obtained from the results of organoleptic assessment and nutrient content. All the collected data were analyzed using analysis of variants and followed by Duncan Multiple Range Test (DMRT) at the 95% confidence level. The results of this study indicate that the effect of temperature and drying time gave no significant interaction effect on the results of organoleptic test including color, aroma, texture, and analysis of water, ash, and iron content. The selected treatment is based on the highest average value of iron (Fe) content with an average value of 0.179 mg / 100 g (S1T1). The selected result of organoleptic analysis including color, smells and texture were found in the SIT2 treatment; color (3.97) is very smooth, smells (3.67) smells of spinach, fine texture (3.67). Meanwhile, the selected test result of nutrient content analysis of water and ash content were found in S3T3 treatment with the value of water content (10.64%) and ash content (8.41%). The higher temperature and the longer of drying time reduced the moisture, ash, and iron content (Fe) produced. Keywords: Green spinach, temperature, duration of dryingABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh suhu dan lama pengeringan terhadap kadar zat besi bayam hijau (Amaranthus spp.). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dua faktor, yaitu: suhu (S) terdiri dari tiga taraf, 50ºC (S1), 60ºC (S2) dan 70ºC (S3), dan waktu (T) yang terdiri dari tiga taraf, 5 jam (T1), 6 jam (T2), dan 7 jam (T3). Analisis data dalam penelitian ini adalah penilaian organoleptik dan kandungan gizi. Data yang diperoleh dianalisis dengan menggunakan analisis ragam (Analysis of Varian) dan dilanjutkan dengan uji Duncan Multiple Range Test (DMRT) pada taraf kepercayaan 95%. Hasil penelitian ini menunjukan bahwa pengaruh suhu dan lama pengeringan memberikan pengaruh interaksi yang tidak nyata terhadap hasil uji organoleptik warna, aroma,tektur serta analisis kandungan kadar air, kadar abu, dan zat besi. Perlakuan terpilih berdasarkan rerata nilai paling tertinggi pada kandungan kadar zat besi (Fe) dengan nilai rerata 0.179 mg/100 g (S1T1). Hasil analisis organoleptik warna, aroma dan tekstur terpilih terdapat pada perlakuan SIT2 yaitu ; warna (3.97) sangat halus, aroma (3.67) berbau khas bayam, tekstur (3.67) halus. Sedangkan hasil uji analisis kandungan gizi kadar air, dan kadar abu perlakuan terpilih pada perlakuan S3T3 yaitu ; kadar air (10.64%) dan kadar abu (8.41%). Semakin tinggi suhu dan semakin lama waktu pengeringan maka akan semakin rendah kadar air, kadar abu dan zat besi (Fe) yang dikandung produk.